Praziquantel and Moxidectin pharmacokinetics in dogs after Helmimax administration - A. A. Smirnov; V. O. Bondarenko; N. I. Soboleva; O. A. Makhlis; A. S. Chagin (Российский паразитологический журнал, 2023)
The purpose of the research is to study Praziquantel and Moxidectin pharmacokinetics in dogs after Helmimax administration.Materials and methods. Helmimax pharmacokinetics was studied on 8 adult male dogs of different breeds aged 2 to 5 years and weighing 15–35 kg. Helmimax was administered orally in the fasted state with a small amount of feed at a dose of 5 mg/kg for Praziquantel and 0.25 mg/kg for Moxidectin at the rate of 1 tablet per 10 kg of body weight. Blood was sampled at various periods after the administration. The collected blood underwent sample processing: formed element and protein precipitation, solid-phase extraction, and microfiltration. The active components were analyzed and detected by the HPLC-MS/MS. Active substances in the blood plasma were determined according to the developed technique which had been validated. The device was calibrated before the measurement.Results and discussion. As a result of the studies, the Praziquantel and Moxidectin pharmacokinetic parameters were calculated. The maximum concentration was 0.240 and 0.130 μg/mL, the time-to-peak concentration was 2.15 and 1.48 hours, and the elimination half-life was 8.41 and 3.61 hours for Moxidectin and Praziquantel, respectively.